Terpinen-4-ol inhibits the proliferation and mobility of pancreatic cancer cells by downregulating Rho-associated coiled-coil containing protein kinase 2. Issue 4 (1st April 2022) - Cao, Wenpeng; Tian, Ruhua; Pan, Runsang; Sun, Baofei; Xiao, Chaolun; Chen, Yunhua; Zeng, Zhirui; Lei, Shan
ABSTRACT: Terpinen-4-ol (T4O), a compound isolated from the seeds of turmeric, has exhibited anti-malignancy, anti-aging, and anti-inflammatory properties in previous studies. However, the specific effects and molecular mechanisms of T4O on pancreatic cancer (PC) cells remain largely unknown. In this study, we demonstrated that T4O markedly suppressed PC cell proliferation and colony formation in vitro and induced apoptosis. Similarly, T4O significantly inhibited the migration and invasion of PC cells in vitro . Through RNA sequencing, 858 differentially expressed genes (DEGs) were identified, which were enriched in the Rhodopsin (RHO)/ Ras homolog family member A (RHOA) signaling pathway. Rho-associated coiled-coil containing protein kinase 2 (ROCK2), a DEG enriched in the RHO/RHOA signaling pathway, was considered as a key target of T4O in PC cells; it was significantly reduced after T4O treatment, highly expressed in PC tissues, and negatively associated with patient outcome. Overexpression of ROCK2 significantly reduced the inhibitory effects of T4O on PC cell proliferation and mobility. Moreover, T4O inhibited cell proliferation in vivo and decreased the Ki-67, cell nuclear antigen, EMT markers, and ROCK2 expression. In conclusion, we consider that T4O can suppress the malignant biological behavior of PC by reducing the expression of ROCK2, thus contributing to PC therapy. Graphical abstract: uf0001